Lending to unhealthy firms in Japan during the Lost Decade: Distinguishing between technical and financial health - Suparna Chakraborty; Joe Peek (Federal Reserve Bank of Boston, 2016)
We investigate the misallocation of credit in Japan associated with banks' evergreening loans, distinguishing between two types of firm distress: (perhaps temporary) financial distress and technical distress, which reflects weak operational capabilities, as indicated by low total factor productivity. We show that previous evidence related to firms' financial health is problematic due to the mixing of loan-demand and loan-supply effects. Using a direct measure of operational health, we provide unambiguous, direct evidence of evergreening behavior, as well as confirming evidence based on the relative impacts on subsequent firm viability of loans by bank types with different incentives to evergreen loans.
Keywords: G21; E44; E51; 330; total factor productivity; bank lending; Japan; zombie firms; financial crisis